2017
DOI: 10.1016/j.radonc.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Patterns-of-failure guided biological target volume definition for head and neck cancer patients: FDG-PET and dosimetric analysis of dose escalation candidate subregions

Abstract: Background To identify the radio-resistant subvolumes in pretreatment FDG-PET by mapping the spatial location of the origin of tumor recurrence after IMRT for head-and-neck squamous cell cancer to the pretreatment FDG-PET/CT. Methods Patients with local/regional recurrence after IMRT with available FDG-PET/CT and post-failure CT were included. For each patient, both pre-therapy PET/CT and recurrence CT were co-registered with the planning CT (pCT). A 4-mm radius was added to the centroid of mapped recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In a smaller cohort of 44 patients enrolled in a prospective phase 2 trial, Leclerc et al [ 55 ] showed that all ten recurrences arose in areas receiving >95% of the dose determined on PET-based plans. A similar finding was reported by Mohamed et al [ 56 ], who hypothesized that a 1-cm margin in addition to the 50% SUV max isocontour on pretreatment FDG PET scans would cover the majority of type A recurrences (according to the authors’ definition, those that arise in the central high-dose area).…”
Section: Discussionsupporting
confidence: 83%
“…In a smaller cohort of 44 patients enrolled in a prospective phase 2 trial, Leclerc et al [ 55 ] showed that all ten recurrences arose in areas receiving >95% of the dose determined on PET-based plans. A similar finding was reported by Mohamed et al [ 56 ], who hypothesized that a 1-cm margin in addition to the 50% SUV max isocontour on pretreatment FDG PET scans would cover the majority of type A recurrences (according to the authors’ definition, those that arise in the central high-dose area).…”
Section: Discussionsupporting
confidence: 83%
“…However, the recurrence volume was not entirely covered by MTV 50 and the SUVmax was not a predictor of recurrence volume location, suggesting that histogram-based FDG-uptake features are not the best suited to guide doseescalation strategies. These results are in line with Mohamed et al [24], who suggested to add a margin of 10 mm to the MTV 50 to cover the majority of recurrences. Nonetheless, the MTV 50+10 also covers most of the GTV.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study, based on 42 patients with a local failure after a radiotherapy treatment, showed that the MTV computed with a threshold of 50% of the maximum SUV of the tumor plus a margin of 10 mm (MTV 50 + 10 ) covers the majority of the recurrence [24]. This volume closely corresponds to the gross tumor volume (GTV), limiting the use of dose escalation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, with somewhat conflicting results and different methodologies, have attempted to correlate the estimated nidus of a post‐treatment failure to the pretreatment PET‐CT avid areas. In the largest cohort, Mohammed et al suggested that a boost to a relatively low 50% threshold subvolume of maximum FDG uptake would cover a fraction of the primary site recurrences, and that an additional margin beyond this relatively low threshold of maximum FDG‐uptake is needed to encompass the majority of relapses . On the opposite, some authors, albeit in smaller cohort studies, indicate that recurrences frequently occur in FDG active areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest cohort, Mohammed et al suggested that a boost to a relatively low 50% threshold subvolume of maximum FDG uptake would cover a fraction of the primary site recurrences, and that an additional margin beyond this relatively low threshold of maximum FDG-uptake is needed to encompass the majority of relapses. 11 On the opposite, some authors, albeit in smaller cohort studies, 12,13 indicate that recurrences frequently occur in FDG active areas. Despite a clear consensus, these studies' cumulative results suggest that, if any, the correlation between post treatment nidus recurrence and pretreatment FDG PET thresholds is seen in the low threshold FDG levels.…”
Section: Discussionmentioning
confidence: 99%